Protocol for EpiCom: A phase 3b/4 study of behavioral outcomes following adjunctive cannabidiol for the management of tuberous sclerosis complex-associated neuropsychiatric disorders (TAND). - Agnies M van Eeghen; Elizabeth A Thiele; Sam Amin; Debopam Samanta; Anna C Jansen; Joanne Stevens; Lisa Moore-Ramdin; Petrus J de Vries (PLoS ONE)
Tuberous sclerosis complex (TSC)-associated neuropsychiatric disorders (TAND) affect ≈90% of individuals with TSC and significantly reduce their quality of life (QoL). However, there are limited studies assessing pharmacotherapy for TAND. A plant-derived highly purified pharmaceutical formulation of cannabidiol (CBD; Epidiolex®/Epidyolex® oral solution) is approved for seizures associated with TSC. Anecdotal evidence also suggests psychiatric, neuropsychological, and behavioral benefits of CBD. EpiCom (Epilepsy Comorbidities; NCT05864846; EU-CT, 2023-507426-17), a multicenter, open-label, phase 3b/4 study, with hybrid decentralized approach, was designed in collaboration with patient advisory groups and healthcare professionals to evaluate behavioral and other outcomes following adjunctive CBD treatment in individuals with TSC-associated seizures. EpiCom will enroll participants, aged 1-65 years (United States [US]) or 2-65 years (United Kingdom [UK], Canada, and Poland), who are starting CBD for seizures and have moderate/severe behavioral challenges according to the Caregiver Global Impression of Severity scale at screening. Participants will receive CBD (up to 25 mg/kg/d based on individual response and tolerability) in addition to their standard of care (SoC) for 26 weeks, after which participants may choose to continue CBD with SoC or SoC alone for an additional 26 weeks. Key efficacy endpoints include change from baseline on the Aberrant Behavior Checklist (e.g., irritability subscale) and the most problematic behavior on the TAND-Self-Report, Quantified Checklist. Changes in executive function, sleep, QoL, family functioning, seizure outcomes (severity, responder rates, seizure-free days), retention rate, and safety will be evaluated. The trial will enroll ≈75 participants at ≈20 sites across the US, the UK, Canada, and Poland. EpiCom will assess the changes in behavioral and other outcomes associated with TAND and seizure outcomes, including overall symptom severity and treatment retention, following adjunctive CBD treatment in individuals with TSC-associated seizures. The results will inform future studies evaluating pharmacotherapy for behavioral outcomes in similar populations.